O estatuto da igualdade racial - Tatiana Dias Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The aim of this paper is to introduce the drafting development of the Racial Equality Statute, established by Law 12.288, of 2010. However, the focus is on the proceedings of the legislative bills which initiated the matter, through the documentary analysis support. As a summary of the bills' changes reported in the paper, the narrative is finished with an outline of the main proposals discarded over ten years of proceedings and those approved and present in the Act. Moreover, an evaluation about the public debate around the Statute approval is featured, ending with a reflection on the prospects and challenges for racial equality policy according to this new legal framework. It is concluded that the law final text is very far from the original proposals and efforts concerning concrete and effective measures to promote racial equality. However, despite these findings, it is estimated that there are conditions for regulatory and political constructions that allow advances in reducing racial inequalities.
Keywords: Z19; 330